A non‐toxic enzyme‐linked immunosorbent assay for aflatoxin B1 using anti‐idiotypic antibodies as substitutes. (18th August 2016) - Hu, Li; Liu, Aiping; Chen, Weifeng; Yang, Hongxiu; Wang, Xiaohong; Chen, Fusheng
Abstract: BACKGROUND: Immunoassays are widely employed techniques to detect aflatoxins since they are rapid, selective and sensitive. One common disadvantage of them is using aflatoxins as standard substances, which may trigger exposure risks to operators and environmental contamination without proper handling. Anti‐idiotypic antibodies (anti‐Ids or Ab2s), also named as internal‐image anti‐Ids, are able to mimic and function as antigens, so a non‐toxic enzyme‐linked immunosorbent assay (ELISA) for aflatoxin B1 (AFB1 ) is developed and validated using anti‐Ids as substitutes. RESULTS: Mouse monoclonal anti‐idiotypic antibody (McAb2) to AFB1 was generated by the hybridoma technique using Fab fragments of rabbit anti‐AFB1 idiotype antibody (Ab1) as immunogen. As indicated by indirect competitive ELISA, McAb2, represented an internal‐image of antigen AFB1, was able to bind Fab with competition to AFB1 . Then, analysis of AFB1 in spiked samples by non‐toxic ELISA using anti‐Ids as substitutes was developed, and it showed no significant differences with comparison to AFB1 as competitive antigens. CONCLUSION: Our work demonstrated that anti‐Ids could be used as internal‐image mimicry of AFB1, and it had potential applications in immunoassays for antigen substitution to reduce operational risk for operators and environmental contamination. © 2016 Society of Chemical Industry